Prognostic Performance of High Expression of KIF23 and Loss of c-CBL in Gastric Cancer Patients: An Immunohistochemical Study - Asmaa Mohamed; Ola Harb; Rehab Hemeda; Mahmoud Sharafedeen; Waleed Abd-Elhady; Ramadan Ali (Middle East Journal of Cancer, 2022)
Background: Kinesin family member 23 (KIF23) has an important role in mitosis of cytoplasmic separation process. Casitas B-lineage lymphoma (c-Cbl) is a protein ligase E3 ubiquitin in tyrosine kinase pathways, involved in numerous cell types.The current study aimed to evaluate the tissue expression of KIF23 and c-Cbl in gastric cancer (GC) tissues and normal gastric mucosa using immunohistochemistry and to investigate the correlation among their expressions, clinicopathological parameters, and the prognosis of patients in order to detect their role in the progression of GC and patientsi prognosis.Method: We conducted this prospective study on 120 samples retrieved from 120 patients; 80 samples were taken from GC patients and 40 from normal gastric mucosa. We assed tissue protein expression of KIF23 and c-Cbl using immunohistochemistry. We evaluated the correlations between KIF23 and C-Cbl expression with clinicopathological and prognostic parameters of patients.Results: KIF23 expression level in GC tissues was positively correlated with high pTNM stage (P = 0.001), larger tumor size (P = 0.010), high tumor grade (P = 0.006), poor overall survival (P < 0.001), disease-free survival rates (P = 0.003), and tumor recurrence after therapy (P = 0.004). c-Cbl expression level in GC tissues was positively correlated with early pTNM stage (P = 0.003), lower tumor grade (P = 0.005), the absence of lymph node metastasis (P = 0.023), good response to therapy (P = 0.002), and the absence of tumor recurrence after the therapy (P = 0.004).Conclusion: The high KIF23 expression and low c-Cbl expression in GC tissues were attributed to progression and poor prognosis in gastric cancer patients.